1997
DOI: 10.1099/0022-1317-78-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus strain A59 is released from opposite sides of different epithelial cell types.

Abstract: Coronaviruses infect humans and animals through epithelial cells of the gastrointestinal and respiratory tracts that serve as their primary target. When studying infections in cultured polarized epithelial cells, we found previously that coronaviruses are released from specific plasma-membrane domains ; thus, mouse hepatitis virus (strain A59 ; MHV-A59) leaves murine epithelial kidney cells from the basolateral surface, whereas release of transmissible gastroenteritis virus from porcine epithelial kidney cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
16
1
Order By: Relevance
“…In contrast, mouse hepatitis virus strain A59, a well-studied murine coronavirus, preferentially infects from the apical surface and buds from the basolateral surface of porcine kidney or human colon carcinoma cells expressing the recombinant MHV receptor and murine kidney epithelial cells. However, the same mouse virus almost exclusively infects and (23,24). We found that HCoV-229E efficiently infected differentiated airway epithelia from the apical surface and also preferentially exited through the same surface.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, mouse hepatitis virus strain A59, a well-studied murine coronavirus, preferentially infects from the apical surface and buds from the basolateral surface of porcine kidney or human colon carcinoma cells expressing the recombinant MHV receptor and murine kidney epithelial cells. However, the same mouse virus almost exclusively infects and (23,24). We found that HCoV-229E efficiently infected differentiated airway epithelia from the apical surface and also preferentially exited through the same surface.…”
Section: Discussionmentioning
confidence: 77%
“…In polarized CaCo-2 intestinal epithelia, HCoV-229E also preferentially infects and exits via the apical surface (D. M. Blau and K. V. Holmes, unpublished data). The mechanism specifying directional release of virions that bud at intracellular membranes is unclear (23,24). Perhaps through evolution the respiratory and enteric coronaviruses adopted an optimal means to spread to neighboring epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation is found with Coronaviridae and Togaviridae. Infection of different epithelial cells with the mouse hepatitis virus resulted in budding from different membrane compartments (32). Also, infection of two different epithelial cell types with Semliki Forest virus or Sindbis virus gave rise to virus release from either the apical or basolateral membrane, depending on the cell type (55).…”
Section: Discussionmentioning
confidence: 99%
“…Cells of human, primate and rodent origin are described to be susceptible for hantavirus infection [11,34,35]. Viruses also show differences in the mechanism and site of entry/release in different epithelial cells [36-39]. MDCK cells are a well established cell culture model to study trafficking and viral pathogenesis in epithelial cells [19,40,41].…”
Section: Discussionmentioning
confidence: 99%